2018
DOI: 10.1093/pch/pxy089
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of scholarly project completion in a paediatric resident program in Canada

Abstract: Background: The primary aims of this study were to: 1) assess barriers and facilitators of completing scholarly projects from residents and faculty mentor perspectives, 2) determine the perceived value of new initiatives designed to support resident scholarly projects and 3) determine if these initiatives led to changes in resident publications. Design and Methods: Between June and September 2014, we surveyed 18 paediatric residents and 41 faculty mentors regarding barriers to resident scholarly project comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The responsibility of balancing these intrinsic and extrinsic motivators falls into the purview of department heads and administrators. Most studies that have aimed to increase research productivity in medicine have targeted residents rather than attending physicians [ 4 , 5 , 6 ]. One model that has effectively increased neurology resident research activity is a compulsory system that requires graduating residents to complete a peer reviewed publication or presentation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The responsibility of balancing these intrinsic and extrinsic motivators falls into the purview of department heads and administrators. Most studies that have aimed to increase research productivity in medicine have targeted residents rather than attending physicians [ 4 , 5 , 6 ]. One model that has effectively increased neurology resident research activity is a compulsory system that requires graduating residents to complete a peer reviewed publication or presentation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This particular limitation also represents the pragmatic nature of such a study, because all institutions implementing their own academic compensation programs will experience similar challenges in generalizability. Traditionally, physician compensation studies have also been performed at single institutions [ 2 , 3 , 4 , 5 , 6 , 9 , 19 ]. Second, three years of follow-up may or may not represent a long enough time course to see an uptick in publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAPN may frequently start with nebulous project ideas they expect to somehow yield feasible SA project designs. 9,10,32 For example, the authors have heard from the SAPN, "I thought it would be interesting to study individuals with condition x." Although this type of orientation may eventually lead to useful descriptive pilot (i.e., more exploratory, descriptive) projects, 5,31,33 the authors have generally concluded that this may comprise an unrealistic desire to study especially terribly complex healthcare topics in initial projects.…”
Section: Spartan Medical Research Journalmentioning
confidence: 99%
“…[1][2][3] Second, the inclusion of community and universitybased residents and faculty in SA projects leads to improved understanding of the medical literature and enhanced clinical practices, arguably producing more "well-rounded" physicians. [4][5][6] Finally, while conducting SA projects during a residency can be quite complex, [7][8][9][10][11] resident physicians, with their "new set of eyes" perspective, may in some ways be in a better position to conduct SA projects to investigate patient care inconsistencies compared to their clinically ex-perienced faculty. 10,[12][13][14] The authors' Statewide Campus System (SCS) in the Michigan State University College of Osteopathic Medicine (MSUCOM) is a consortium of graduate medical residency programs across the state of Michigan.…”
Section: Introductionmentioning
confidence: 99%